Estudo de diferentes tratamentos da caulinita para possível aplicação como adsorvente do corante têxtil C.I. Reactive Blue 203 - Sotiles, Anne Raquel (2017)
The kaolinite is a clay mineral used in several industrial sectors and, due to the high availability in the earth's crust, chemical modifications are made to obtain different structures of the material in order to expand its use. Activations were carried out with phosphoric and sulfuric acids at concentrations of 5 and 10 mol L-1, and thermal treatments at 850, 1100 and 1200ºC for the application of this clay in the adsorption of Reactive Blue 203 textile dye. The samples were characterized by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA), Differential Thermal Analysis (DTA) and Scanning Electron Microscopy (SEM). In the FTIR spectra of the calcined samples, the characteristic hydroxyl absorptions disappeared, as well as the appearance of vibrations attributed to metacaulinite, which is formed from calcination of kaolinite. By XRD, it was possible to confirm the changes in the structure, since the diffractogram showed a characteristic of amorphous material when calcined at 850 °C, while in the temperatures of 1100 and 1200 °C the material returned to present crystalline structure, due to the formation of the mullite. These changes are also evident in the thermal analysis, and the event occurring in the thermogravimetric curve between 420 ºC and 700 ºC refers to the dehydroxylation of the material and, consequently, to the formation of metakaolin. The differential thermal analysis showed an exothermic peak in the region of 1000 ºC, corresponding to the conversion of metacaulinite to mullite. However, SEM analysis did not show changes in material morphology. The zero charge point obtained for kaolinite was 4.41, corresponding to the pH value at which the surface charge is zero, and at pH values higher than that kaolinite will be more propitious to adsorb cationic substances and in values of pH lower, anionic. The kaolinite presented higher amount of acidic sites, since both analyzes resulted in pH values lower than 7, characteristic of clay minerals with lamellar structure, due to the presence of internal hydroxyls and aluminum, since it is an aluminosilicate. In the adsorption test with the Reactive Blue 203 textile dye, the untreated kaolinite stood out in the other samples, with better adjustment of the Sips isotherm and pseudo second order kinetics. The thermodynamic parameters indicate that it is a spontaneous and endothermic process and evidence that a chemical adsorption occurs.